2011
DOI: 10.1007/s10147-011-0222-6
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg3 inhibits CXCR4 expression and related migrations in a breast cancer cell line

Abstract: This work suggests that Rg3 is a new CXCR4 inhibitor from a natural product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…The high level of CXCR4 mRNA in tumor cells is believed to be involved in their survival under hypoxia [28]. Further, overexpression of CXCR4 has been associated with metastases formation and poor prognosis of patients with breast and other types of cancer [29][30][31], which explains the significant interest towards CXCR4 inhibitors [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high level of CXCR4 mRNA in tumor cells is believed to be involved in their survival under hypoxia [28]. Further, overexpression of CXCR4 has been associated with metastases formation and poor prognosis of patients with breast and other types of cancer [29][30][31], which explains the significant interest towards CXCR4 inhibitors [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The equal levels of CXCR4 in treated and control MCF10A cells at 7h implied that the reduction in expression of CXCR4 in these cells required more time. Even though there are no data about saponins from TT, CXCR4 downregulation at protein level has been detected after treatment of cells with saponins extracted from various other plants like ginseng [32].…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenoside Rg3 combined with capecitabine enhanced antiangiogenic efficacy in breast cancer in mice and exhibited improved antitumor effects and reduced toxicity (15). In addition, ginsenoside Rg3 was shown to inhibit CXCR4 expression and related migrations in the MDA-MB-231 breast cancer cell line (16). Rg3 promoted the efficacy of cisplatin by inhibiting heme oxygenase 1 and NAD(P)H dehydrogenase (quinone 1) expression in CT-26 colon cancer cells and protected the kidney and liver against tissue damage by preventing cisplatin-induced intracellular reactive oxygen species generation (17).…”
Section: Discussionmentioning
confidence: 99%
“…Using indirect investigational techniques, the influence of Rg3 on CXCR4 expression has been reported in cultured MDA-MB-231 breast cancer cell line (Chen et al 2011). Based on Immunohistochemistry, chemotaxis, and wound healing mobility assays, it has been shown that Rg3 treatment at nontoxic dose range elicits a weak CXCR4 staining indicative of downregulation of the receptor, concomitant with diminutions in the number of migrated cells in CXCL12-elicited chemotaxis, and reduction in the width of the scar in wound healing assay attesting Rg3 efficacy with CXCR4 inhibition (Chen et al 2011). …”
Section: Chemokine Receptors and Microenvironmentmentioning
confidence: 99%